기업지배구조평가등급이 실제이익조정에 미치는 영향 - 박애영(Park, Ae-Young) (대한경영학회지, 2013)
본 연구는 2006년부터 2010년까지 유가증권 시장에 계속 상장되어 있는 제조업에 속하는 12월말 결산법인을 대상으로 우수한 기업지배구조가 경영자의 실제이익조정을 통제하는 기능을 하는지를 고찰한다. 본 연구에서는 개별기업의 기업지배구조의 특성을 전반적으로 고려한 한국기업지배구조원 (CGS)의 기업지배구조평가등급을 기업지배구조의 우수성의 대용치로 활용하고, Cohen과 Zarowin(2010)에 따라 측정된 실제이익조정 측정치를 경영자의 이익조정의 대용치로 활용하여 관련 선행연구를 확장하였다. 분석결과, 기업지배구조평가등급이 우수한 기업에서는 실제이익조정이 유의적으로 감소하는 것으로 나타났다. 또한, 기업지배구조가 우수하다고 평가받은 기업은 경영자지분율이 증가함에 따라 경영자의 실제이익조정 정도가 유의적으로 감소하는 것으로 나타났다. 반면, 기업지배구조가 우수하다고 평가받지 않은 기업의 경우 경영자지분율의 증가가 유의적인 영향을 미치지 못하는 것으로 나타났다. 연구결과를 통해 경영자지분율이 실제이익조정에 미치는 영향이 개별기업의 지배구조의 우수성에 따라 달라질 수 있음을 보임으로서 우수한 기업지배구조가 이익조정 행위와 같은 대리인문제를 통제하는 효과가 있다는 실증증거를 제공할 수 있었다. This paper analyzes empirically that how much the level of corporate governance has an effect on the real earnings management by using KOSPI-listed manufacturing firms from 2006 to 2010. Unlike the prior research, the level of corporate governance was measured by firm’s corporate governance ratings evaluated comprehensively from Korea Corporate Governance Service(CGS) and the real earnings management measures was based on Cohen and Zarowin(2010) model. As a results, this study finds that the degree of firm’s real earnings management tends to be lower when a firm has a good corporate governance ratings. It represents that good corporate governance is effective controlling mechanism to reduce real earnings management. Another results suggests that as the managerial ownership increases, real earnings management tends to decrease significantly when a firm has a good corporate governance ratings. But, the results shows that managerial ownership does not affect significantly on real earnings management when a firm has a poor corporate governance evaluation ratings. The empirical results of this paper suggests that the good corporate governance can play an important role in controlling firm’s agency problem and manager’s opportunistic behaviors. KCI Citation Count: 16